Nuclear interactions in a heterokaryon: insight from the model Neurospora tetrasperma - Samils, Nicklas (The Royal Society, 2014)
A heterokaryon is a tissue type composed of cells containing genetically different nuclei. Although heterokaryosis is commonly found in nature, an understanding of the evolutionary implications of this phenomenon is largely lacking. Here, we use the filamentous ascomycete Neurospora tetrasperma to study the interplay between nuclei in heterokaryons across vegetative and sexual developmental stages. This fungus harbours nuclei of two opposite mating types (mat A and mat a) in the same cell and is thereby self-fertile. We used pyrosequencing of mat-linked SNPs of three heterokaryons to demonstrate that the nuclear ratio is consistently biased for mat A-nuclei during mycelial growth (mean mat A/mat a ratio 87%), but evens out during sexual development (ratio ranging from 40 to 57%). Furthermore, we investigated the association between nuclear ratio and expression of alleles of mat-linked genes and found that expression is coregulated to obtain a tissue-specific bias in expression ratio: during mycelial extension, we found a strong bias in expression for mat A-linked genes, that was independent of nuclear ratio, whereas at the sexual stage we found an expression bias for genes of the mat a nuclei. Taken together, our data indicate that nuclei cooperate to optimize the fitness of the heterokaryon, via both altering their nuclear ratios and coregulation genes expressed in the different nuclei.